ANALISIS FAKTOR YANG MEMPENGARUHI PRODUKSI DAN PENDAPATAN PETANI GARAM DESA KUSAMBA KECAMATAN DAWAN KABUPATEN KLUNGKUNG - Artawan, Gede Jaya; Wenagama, i Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.01.TAHUN 2020DO - 10.24843/EEB.2020.v09.i01.p05, 2020)
One of the traditional agricultural commodities in Bali, especially in Kusamba Village, Dawan District, Klungkung Regency is salt, which is known as a source of livelihood in Kusamba Village. The purpose of this study was to analyze the factors that influence the production and income of salt farmers in Kusamba Village, Dawan District, Klungkung Regency. The data used in this study are primary data obtained by conducting interviews with 62 salt farmers in Kusamba Village. The data analysis technique used in this study is path analysis. The test results showed that the area of ??land, labor and capital had a positive and significant effect on the amount of salt production in Kusamba Village, Dawan District, Klungkung Regency. Land area, labor, capital and salt production have a positive and significant effect on the income of salt farmers in Kusamba Village, Dawan District, Klungkung Regency. Land area, labor, and capital have a positive effect on the income of salt farmers through salt production in Kusamba Village, Dawan District, Klungkung Regency.